EFEKTIVITAS PENGGUNAAN MODUL LAJU REAKSI BERBASIS INKUIRI TERBIMBING TERINTEGRASI EKSPERIMEN UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Hidayat, Taufik (RC-INSTITUT, 2019)
The reaction rate is a factual, conceptual and procedural chemical material. One method that can be applied in this learning is an experimental method that is integrated in learning. This study aims to reveal the effectiveness of integrated inquiry-based integrated reaction rate module experiments and science process skills on the learning outcomes of XI MIPA students at SMAN 7 Padang. This study included quasi-experimental research with aresearch non-equivalent control group design. The subjects in this study were students of class XI MIPA 6 and MIPA 7. Subjects were selected using purposive sampling technique. The object of research is student learning outcomes.. The research instrument used was the test of student learning outcomes namely the initial test (pretest) and the final test (posttest) in the form of 20 objective questions in accordance with the learning objectives. The average difference between initial values ​​and the final test of the experimental class (53.53) and the control class (35.7). Based on data analysis shows that the subject is normally distributed and homogeneous so that it can be carried out t-test, obtained value t ≥ t1-α that is 4,432> 1.66901 then reject Ho. This means that the experimental class learning outcomes are higher than the control class significantly. This is also supported by the experimental class n-gain value of 0.73 in the high category. Based on the data analysis shows the integrated inquiry-based rate rate module integrated experimentation and science process skills proved to be effective against learning outcomes with a high category.   Keywords: effectiveness, modules, guided inquiry, integrated experimentation, learning outcomes.